Efectividad de la fertilización complementada con enmiendas, en el crecimiento, rendimiento y rentabilidad del cultivo de arroz (Oryza sativa) - Zambrano Loor, José Luis (2024)
The objective of the work was to evaluate the effectiveness of fertilization supplemented with amendments on the growth, yield and profitability of the rice crop (Oriza sativa). An experiment was developed during the 2022 and 2023 seasons. The treatments evaluated were: T1: Fertilization conventional + Saline Corrector, T2: Conventional fertilization + Vine minerals, T3: Conventional fertilization + Plaster, T4: Conventional fertilization + Humiful, T5: Conventional fertilization + Wayra, T6: Hill Fertilization, T7: Conventional fertilization, T8: Control. A randomized complete block design (DBCA) was used. The main variables recorded were plant height (AP), chlorophyll (SPAD), fertile tillers (MF), 1000 grain weight (PMG), grain yield (RG) and economic profitability (RE). The data were analyzed using ANOVA and separation of means with Tukey's test (α = 0.05). The treatments significantly influenced (p<0.05) the growth and yield of rice in both planting seasons, where the fertilization treatments with amendments (T1-T5) were superior to the conventional fertilization treatments (T6-T7) and the control treatment. (T8). On average, the increase in yield with the use of amendments was greater than 15% in relation to the treatments without amendments and the control. The economic profitability was greater than 60% with amendments in 2022 and greater than 30% in the 2023 season. The use of amendments is effective in enhancing the growth, yield and profitability of rice, and their use does not represent an economic disadvantage for the farmer.